Lingkungan Belajar, Perilaku Belajar dan Tingkat Pemahaman Pengantar Akuntansi dalam Proses Pembelajaran Daring - Puspasari, Dewa Ayu Dwita; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2023)
Changes in various aspects of activities occurred at the beginning of 2020 due to the Corona virus Disease (Covid-19) pandemic. Changes in the learning process switch to online (online). The research aims are to focus on understanding the influence of the learning environment and learning behavior on the level of understanding of introductory accounting. The sample was selected as many as 165 people through a survey with students of the Bachelor of Accounting Study Program, Faculty of Economics and Business, Udayana University as the population. Multiple linear regression analysis was chosen to be the technique for conducting data analysis. This research found that there is a positive influence of the learning environment and learning behavior on the level of understanding of introductory accounting through online. The implications of this research finding support the attribution theory regarding the level of understanding that is influenced by various external and internal factors. Keywords: Learning Environment; Learning Behavior; Level of Understanding of Introduction to Accounting